Hydroxy‐Functionalized Hypercrosslinked Polymers (HCPs) as Dual Phase Radioactive Iodine Scavengers: Synergy of Porosity and Functionality. Issue 11 (6th September 2022) - Samanta, Partha; Dutta, Subhajit; Let, Sumanta; Sen, Arunabha; Shirolkar, Mandar M.; Ghosh, Sujit K.
Abstract: Large‐scale nuclear power plant production of iodine radionuclides ( 129 I, 131 I) pose huge threat in the events of nuclear disaster. Effective removal of radioiodine from nuclear waste is one of the most critical challenge because of the drawbacks of state‐of‐the‐art adsorbents such as high cost, low uptake capacity and non‐recyclability. Herein, two hydroxy‐functionalized (‐OH) hypercrosslinked polymers (HCPs), namely HCP‐91 and HCP‐92, have been synthesized and employed towards capture of iodine. High chemical stability along with synergistic harmony of high porosity and functionality of these materials makes them suitable candidates for capture of iodine from both vapor phase and water medium. Moreover, both the HCPs showed superior iodine removal performance from water in terms of fast kinetics and high removal efficiency (2.9 g g −1 and 2.49 g g −1 for HCP‐91 and HCP‐92 respectively). The role of functionality (‐OH groups) and porosity has been established with the help of HCP‐91, HCP‐92 and non‐functionalized biphenyl HCP for the efficient capture of I3 − ions from water. In addition, both HCPs exhibited excellent selectivity and recyclability towards triiodide ions, rendering the potential of these materials towards real‐time applications. Lastly, Density functional theoretical studies revealed key insights and corroborate well with the experimental findings. Abstract : Efficient capture of radioactive iodine from both vapour and aqueous phase has been achieved by hydroxy‐functionalized HCPs with a synergic contribution of functionality and porosity of the HCPs.